MORPHOLOGICAL AND BIOCHEMICAL CHANGES IN WISTAR RAT LIVERS AFTER CLOFIBRATE TREATMENT - Bogdanska, Jasna; Toseska Trajkovska, Katerina; Labudovic, Danica; Cekovska, Svetlana; Topuzovska, Sonja; Petrusevska, Gordana (Journal of Morphological Sciences, 2018)
The aim of our study was to determine whether short-term administration of clofibrate can lead to morphological changes in the Wistar rat livers and weather these changes were accompanied by changes in the specific activity of the enzymes involved in oxidative stress.  Male Wistar rats divided in two groups: control and experimental were treated with saline solution and clofibrate respectively (250 mg/1000 g/ day) for 12 days. Tissue liver samples were taken for morphological examination and liver homogenates and sub-cellular fractions were used for measurement of proteins, reactive oxygen species (ROS) producing and ROS scavenging enzyme activities.  Following clofibrate treatment, liver histopathology in the treated group has shown deranged liver architecture, focal necrosis and presence of atypical lymphocytes. Electron light mitochondrial matrix and increased number of peroxisomes and mitochondria were also observed. These changes were accompanied by increase of the specific activity of ROS producing enzymes (urate oxidase and palmitoyl CoA oxidase). The most prominent increase of the activity with the increase of relative sub-cellular distribution was observed in the peroxisomal fraction (LMF). Specific activity of catalase was increased, whereas superoxide dismutase and glutathione peroxidase have shown almost a double decrease.  Morphological changes in the liver accompanied by ROS production which has prevailed over their removal pointed to a conclusion that clofibrate can cause morphological changes accompanied by biochemical changes.